High‐performance liquid chromatography separation of unsaturated organic compounds by a monolithic silica column embedded with silver nanoparticles. Issue 16 (15th July 2015) - Zhu, Yang; Morisato, Kei; Hasegawa, George; Moitra, Nirmalya; Kiyomura, Tsutomu; Kurata, Hiroki; Kanamori, Kazuyoshi; Nakanishi, Kazuki
<x xml:space="preserve">Abstract</x> The optimization of a porous structure to ensure good separation performances is always a significant issue in high‐performance liquid chromatography column design. Recently we reported the homogeneous embedment of Ag nanoparticles in periodic mesoporous silica monolith and the application of such Ag nanoparticles embedded silica monolith for the high‐performance liquid chromatography separation of polyaromatic hydrocarbons. However, the separation performance remains to be improved and the retention mechanism as compared with the Ag ion high‐performance liquid chromatography technique still needs to be clarified. In this research, Ag nanoparticles were introduced into a macro/mesoporous silica monolith with optimized pore parameters for high‐performance liquid chromatography separations. Baseline separation of benzene, naphthalene, anthracene, and pyrene was achieved with the theoretical plate number for analyte naphthalene as 36 000 m−1. Its separation function was further extended to cis/trans isomers of aromatic compounds where cis/trans stilbenes were chosen as a benchmark. Good separation of cis/trans‐stilbene with separation factor as 7 and theoretical plate number as 76 000 m−1 for cis‐stilbene was obtained. The trans isomer, however, is retained more strongly, which contradicts the long‐ established retention rule of Ag ion chromatography. Such behavior of Ag nanoparticles embedded in a silica column can be attributed to the differences in the molecular geometric configuration of cis/trans stilbenes.